GRAMMATICAL AND STYLE FEATURES OF RELIGIOUS LECTURES (Universal International Scientific Journal, 2026)
This article analyzes the grammatical and stylistic features of religious discourse. The study scientifically illuminates the syntactic structure, lexical-semantic features, use of grammatical means, and possibilities of stylistic expression of the discourse texts formed within the framework of religious discourse. It also analyzes the communicative functions of rhetorical means, expressive speech units, repetition, exclamation, and appeal forms in religious discourse. The results of the study are of significant scientific importance in determining the linguistic nature of religious speech genres and elucidating the functional-stylistic features of religious discourse.
Keywords: religious discourse, religious lecture, speech genre, grammatical features, stylistic devices, syntactic structure, rhetorical methods, communicative effect, religious speech.